-4z-4z=3z+3+3z

Simple and best practice solution for -4z-4z=3z+3+3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4z-4z=3z+3+3z equation:


Simplifying
-4z + -4z = 3z + 3 + 3z

Combine like terms: -4z + -4z = -8z
-8z = 3z + 3 + 3z

Reorder the terms:
-8z = 3 + 3z + 3z

Combine like terms: 3z + 3z = 6z
-8z = 3 + 6z

Solving
-8z = 3 + 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-8z + -6z = 3 + 6z + -6z

Combine like terms: -8z + -6z = -14z
-14z = 3 + 6z + -6z

Combine like terms: 6z + -6z = 0
-14z = 3 + 0
-14z = 3

Divide each side by '-14'.
z = -0.2142857143

Simplifying
z = -0.2142857143

See similar equations:

| 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 | | 4z=2.5+2.7 | | 27=0.5x(2+7) | | 9-1/2b=5+8/2b | | xx=42 | | 4k^2-13k+3=0 | | 8-(4y-9)=5-5y | | -3x+22/2= | | (x-1/2)=(2-x/3) | | 5.4/-4.5y | | -10?4(3p?10)=18 |

Equations solver categories